PROSES KOREOGRAFI TARI BLAKASUTA - Ardiansah, Ardiansah (Universitas Negeri Semarang, 2014)
Koreografi tari Blakasuta merupakan karya tari baru yang digarap oleh mahasiswa jurusan Pendidikan Sendratasik melalui mata kuliah koreografi. Idenya berasal dari ungkapan masyarakat di kabupaten Banyumas yang menggambarkan sikap keterusterangan. Permasalahan yang diangkat dalam penelitianiniadalahtahapan proses koreografitariBlakasuta serta faktor pendorong dan penghambatnya. Adapun tujuanpenelitianadalah; 1) Mengetahui proses komposisi, koreografi, iringan, tata rias busana TariBlakasuta; 2) Inginmengetahui faktor pendukung dan penghambatproses koreografi tari Blakasuta. Hasil penelitian menunjukkan bahwa proses koreografi tariBlakasutameliputi dua aspek, yaitu aspek pokok koreografi dan aspek pendukung koreografi. Aspek pokok koreografi terdiri dari; 1) Proses penemuan ide; 2) Pembuatan Konsep; 3) Eksplorasi; 4) Komposisi; 5)Improvisasi. Sedangkan aspek pendukungantara lain gerak, tenaga, iringan,waktu, tata rias busana. Semua proses itudigunakanhinggamenghasilkankaryatariBlakasuta. Blakasutachoreography dance is a new creation dance created by collegian of SendratasikEducation Department of Choreography course. This dance inspired from the utterance of Banyumas society that describing. The problem of this research was the process of choreography Blakasuta dance and supporting factors also retarded factors of this choreography dance process. The aim of this research was 1) to know process composition, choreography, music, make up and the clothes of Blakasuta dance; 2) to know the supporting and retarded factors in the choreography process of Blakasuta . The result of this research showed that choreography process of Blakasuta dance consist of two important aspects, they were the main aspect and supporting aspect of choreography. The main aspect of choreography consists of 1) the process of idea; 2) draffing; 3) Exploration; 4) composition; 5) Improvisation.. Whilesupporting aspectsof choreographyincludemotion, energy, space, andtime, makeup and clothes. All processes wereusedtoproduce aBlakasuta dance.